Students’ perceptions concerning the learning environment based on biology teachers’ TPACK - Cut Intan Evtia Nurina; R. Riandi; Ari Widodo; Hendra Yulisman (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Research about students’ perceptions concerning the learning environment based on biology teachers’ TPACK still limited. The purpose of this study was to obtain information about the impact of biology teachers’ TPACK on students’ perceptions concerning their learning environment. TPACK scores were obtained from instrument in the form of multiple-choice test questions. Furthermore, students’ perceptions of their learning environment were obtained using a Likert scale questionnaire. Two biology teachers were used as research samples determined by purposive sampling, which is referring to their TPACK score. Furthermore, students who became the research sample were students from those two teachers that consists of 64 students. The analysis results show that teachers have different TPACK ability at the level of TPACK forming components. Furthermore, there are differences in students' perceptions based on their teachers' TPACK ability. The results were indicated teacher professionalism, in this case, TPACK has the impact on learning environment. Therefore, teachers, schools, government, and education providers are expected to give special attention to teacher professionalism.